Feedback for Programming Assignments Using Software-Metrics and Reference Code. (25th December 2013) - Koyya, Pardha; Lee, Young; Yang, Jeong
Abstract : Feedback for student programming assignments on quality is a tedious and laborious task for the instructor. In this paper, we make use of few object-oriented software metrics along with a reference code that is provided by the instructor to analyze student programs and provide feedback. The empirical study finds those software metrics that can be used on the considered programming assignments and the way reference code helps the instructor to assess them. This approach helps the instructor to easily find out quality issues in student programs. Feedback to such assignments can be provided using the guidelines which we will be discussing. We also perform an experimental study on programming assignments of sophomore students who were enrolled in an object-oriented programming course to validate our approach.